1990
DOI: 10.1159/000169958
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Microbiological Evaluation of a Postdilutional Hemofiltration System with In-Line Production of Substitution Fluid

Abstract: Safety and efficacy of a recently developed hemofiltration (HF) system with in-line production of substitution fluid (GHS-10; Gambro, Lund, Sweden) based on a sterilizing filtration of acetate buffered dialysate has been evaluated in 4 patients over a 6-month period. Two patients were prematurely excluded from the study: 1 because of acetate intolerance and the other because of kidney transplantation. Two patients completed the study (240 HF sessions). Treatment adequacy was maintained in the 2 medium term tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…To maintain optimal filtration capacity, by preventing membrane fouling and microbial-derived product accumulation, the ultrafilter must be disposed in a crossflow filtration configuration as presented in figure 5. To reduce the risk of device failure, two filters disposed in series on the dialysate pathway, as shown in figure 4b are recommended [56]. Large differences in the retention capacity of ultrafilters may exist for the same type of ultrafilter.…”
Section: Ultrafilters Ultrafiltration and Cold Sterilizationmentioning
confidence: 99%
“…To maintain optimal filtration capacity, by preventing membrane fouling and microbial-derived product accumulation, the ultrafilter must be disposed in a crossflow filtration configuration as presented in figure 5. To reduce the risk of device failure, two filters disposed in series on the dialysate pathway, as shown in figure 4b are recommended [56]. Large differences in the retention capacity of ultrafilters may exist for the same type of ultrafilter.…”
Section: Ultrafilters Ultrafiltration and Cold Sterilizationmentioning
confidence: 99%
“…On-line filtration of dialysate with a 40,000 dalton cut-off polyamide hernofilter resulted in a reduction of the incidence of febrile episodes of unknown origin from 3.6 to 1.9% in patients dialyzed with low-flux plate dialyzers (80). Recently it was shown that on-line filtration of substitution fluid resulted in the absence of pyrogenic reactions in 240 hemofiltration sessions with a total infusion volume of over 7,000 L (76). These studies indicate that on-line filtration of dialysate and substitution fluid reduces the incidence of PR in hemodialysis and hemofiltraiion, respectively.…”
Section: Acute Effectsmentioning
confidence: 95%
“…Several recent studies have shown that on-line ultrafiltration is effective at reducing bacterial counts and endotoxin levels in dialysate (73)(74)(75)(76)(77). Results of these studies are summarized in Table 2.…”
Section: Reduction Of Bacterial Counts and Endotoxin Levels By On-linmentioning
confidence: 99%
“…This technically advantageous and cost-competitive production of substitution fl uid has been employed to develop various forms of high-effi ciency HDF modalities (postdilution, predilution, mixed-dilution, middilution). The generic term commonly used to characterize these modalities is ol-HDF [15][16][17].…”
Section: Rationale For Online Hemodiafiltrationmentioning
confidence: 99%